A polymorphism in IL4 may associate with sensory neuropathy in African HIV patients - Wadley, A.; Kamerman, P.; Chew, C.; Lombard, Z.; Cherry, C.; Price, Patricia (2013)
Introduction Animal and in vitro models of HIV-associated sensory neuropathy suggest an inflammatory etiology. Previous genetic association studies of HIV-SN have been in small Caucasian or Asian cohorts. We assessed cytokine single nucleotide polymorphisms (SNPs) in a Black Southern African cohort. Method 342 black HIV-positive Southern Africans were recruited. 190 individuals had HIV-associated sensory neuropathy and 152 did not. DNA samples from all participants were genotyped for cytokine SNPs identified in studies of HIV disease and/or neuropathy. Results IL4-590*T associated with an increased prevalence of HIV-SN including following correction for age, height and CD4 T-cell count. No other cytokine SNPs assessed displayed an association. Discussion We identified a novel association between IL4-590*T and HIV-SN in African HIV-positive patients which warrants further investigation. © 2013 Elsevier Ltd.